1998
DOI: 10.1136/jmg.35.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of 8p23.1: a cytogenetic anomaly with no established clinical significance.

Abstract: We present seven families with a cytogenetic duplication ofthe short arm of chromosome 8 at band 8p23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…Dhooge et al [1994] reported a mother and her two children with a tandem duplication of band 8p22, either 8p22-8p23 or 8p21.3-8p22, with mild mental retardation, facial anomalies and short stature. Interstitial duplication within 8p23 have been reported including speci®cally duplication within band 8p23.1, associated with mild dysmorphology [Gibbons et al, 1999] or normal phenotype [Barber et al, 1998] and duplication of band 8p23.2 associated with a normal phenotype [Engelman et al, 2000]. The clinical features seen in the patients presented here could also be due to the presence of mosaicism in the patient [Woods et al, 1994] and the effect this has in individual tissues.…”
Section: Discussionmentioning
confidence: 55%
“…Dhooge et al [1994] reported a mother and her two children with a tandem duplication of band 8p22, either 8p22-8p23 or 8p21.3-8p22, with mild mental retardation, facial anomalies and short stature. Interstitial duplication within 8p23 have been reported including speci®cally duplication within band 8p23.1, associated with mild dysmorphology [Gibbons et al, 1999] or normal phenotype [Barber et al, 1998] and duplication of band 8p23.2 associated with a normal phenotype [Engelman et al, 2000]. The clinical features seen in the patients presented here could also be due to the presence of mosaicism in the patient [Woods et al, 1994] and the effect this has in individual tissues.…”
Section: Discussionmentioning
confidence: 55%
“…In most cases this duplication was believed to be a benign variant with no phenotypic effect 12 and described as an euchromatic variant (EV). 13,14 This was disputed by Tsai et al 15 who reported on 12 patients with an 8p23 duplication and a significant phenotype comprising mainly heart defects. Nevertheless, the clinical features of these patients were not evocative of KS.…”
Section: Discussionmentioning
confidence: 70%
“…A limited number of studies reported the presence of specific large duplications and deletions that were not apparently related to disease (e.g., Barber et al 1998;Engelen et al 2000). For example, a deleted region originally thought to be associated with ovarian cancer was later found to also be present in healthy in-dividuals (Lin et al 2000).…”
Section: Cnvs In Normal Individualsmentioning
confidence: 99%